Potential Surgical Exposure of the Parapharyngeal Internal Carotid Artery by Endonasal, Transoral, and Transcervical Approaches - Tanjararak, Kangsadarn; Upadhyay, Smita; Thiensri, Thanakorn; Muto, Jun; Roongpuvapaht, Boonsam; Prevedello, Daniel M.; Carrau, Ricardo L. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Endoscopic and endoscopic-assisted approaches to the parapharyngeal space have been reported; however, their potential for vascular exposure has not been previously assessed. This study aims to compare the potential exposure and control of the parapharyngeal internal carotid artery (ppICA) via various approaches.Design and Main Outcome Measures Ten cadaveric specimens were dissected bilaterally, exposing the ppICA via endonasal, transoral, and transcervical approaches. Length of the exposed vessel and potential control were assessed (feasibility and time required to place an encircling suture).Results Endoscopic transoral and transcervical–transmandibular approaches expose a significantly longer segment of the ppICA (6.89 and 7.09 cm) than the transoral and endonasal approaches. Vascular control was achieved via endoscopic-endonasal, endoscopic-transoral, and open techniques in 121.6, 64.8, and 5.2 seconds, respectively.Conclusion Histopathology, goals of surgery, and familiarity of the surgeon with each technique may ultimately determine the choice of approach; however, this study suggests that exposure of the ppICA by endoscopic-assisted transoral approach is comparable to that of a transcervical–transmandibular approach. Vascular control was feasible under elective circumstances. However, the difficulty varied widely, potentially reflecting the challenges of controlling an injured ppICA. However, one must note that active bleeding obscures the surgical field in ways that may impair ppICA control. Furthermore, the results may not reflect clinical scenarios where tumor distorts the surgical field.Nonetheless, the study suggests that, in properly selected patients, the endoscopic-assisted transoral approach avoids problems associated with unsightly scars, mandibular osteotomy, and facial nerve manipulation, whereas, the transcervical–transmandibular approach offers the swiftest vascular control.
Keywords: parapharyngeal space; internal carotid artery; endoscopic endonasal approach; endoscopic transoral approach; transcervical approach